Rights and Position of Home Children In The Sanahu Community of West Part of Seram District - Latupono, Barzah; Laturette, Adonia Ivonne; Radjawane, Pieter (Batulis Civil Law Review, 2023)
Introduction: The offspring of a husband and wife being taken as children for another family, whether close relatives or distant relatives based on an agreement which of course gives rise to the rights and position of the adopted child, for this reason it is necessary to establish the rights and position of the child. so it won't cause problems in the future.Purposes of the Research: To find out and analyze the rights and position of returning children in the Sanahu Community, West Seram Regency.Methods of the Research: This research was conducted using an empirical juridical approach which is a descriptive qualitative analysis study. The research attempts to describe the rights and position of returning children in the Sanahu Community, West Seram Regency. The workings of the empirical juridical or sociological juridical method in this research proposal, namely from the results of collecting and discovering data and information through literature study of the basic assumptions or presumptions used in answering the problems in this research, then inductive-verification testing is carried out on the latest facts existing in society.Results of the Research: The results of the research show that the rights and position of children returning home in the Sanahu Community of West Seram Regency are regulated based on customary rules that developed in Sanahu Village where adopted children will be classified as legitimate children of the parents who adopted them and have the position of biological children so that they have the right to the inheritance of that person. The parents adopted him, but the assets he inherited were only the joint assets of his adoptive parents. The child's inherited assets did not have the right to inherit them.